ANALISIS PERUBAHAN PENGGUNAAN LAHAN KOTA TOMOHON PROVINSI SULAWESI UTARA (The Land Use Change Analysis of Tomohon City, North Sulawesi Province) - Mayheard Engel Lord Mogi; Theodora Katiandagho; Sandra Pakasi (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2023)
This study aims to describe and determine the extent of changes in agricultural to non-agricultural land use from 2012 to 2021 in Tomohon City, to analyze the factors that influence changes in agricultural to non-agricultural land use in Tomohon City and to identify and analyze the efforts implemented. to control changes in land use from agriculture to non-agriculture in Tomohon City. This research was conducted in Tomohon City. The data used in this study are primary data and secondary data. Primary data was obtained from interviews, while secondary data was obtained from BAPPEDA, BPS, District Officials, Related Agencies and Library Studies. Methods of data analysis using Qualitative Descriptive Analysis and Overlay Method. The results showed that land use in 2012 was dominated by Green Open Space land use with a percentage of 76.05% and a land use area of ​​11279.3 ha. Land use in 2021 is dominated by Green Open Space land use with a percentage of 74.90% and an area of ​​land use reaching 11155.52 ha.